The Influence of Librarian Competence on the Quality of Library Services at the Library and Archives Service in Bengkalis Regency - Suryani Ardila; Johan Andriesgo (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This research aims to: (1) Find out how much competence librarians in the Bengkalis Regency Library and Archives Service have; (2) Find out how high the quality of library services is at the Bengkalis Regency Library and Archives Service; (3) Find out how much significant influence librarian competence has on the quality of library services at the Bengkalis Regency Library and Archives Service. This research is field research with variables The data in this research was taken using documentation and questionnaires. The results of the research show that: (1) The competence of librarians in the Bengkalis district library and archives service is categorized as good, this can be proven by the percentage value of the questionnaire regarding librarian competence, namely 77.7%; (2) The quality of library services in the Bengkalis district library and archives service is categorized as good, this can be seen from the percentage value of library service quality, namely 79.8%; (3) There is a significant influence between librarian competence on the quality of library services, this can be proven by analysis of the coefficient of determination where the coefficient of determination is 0.741. This shows the understanding that changes in the level of quality of library services (Y) are 74.1% influenced by Librarian Competency (X), while the remaining 25.9% (100% - 74.1%) is explained by other causes.